Menuju Model Ideal Penyidikan Multiparty di Indonesia: Towards an Ideal Model of Multiparty Investigation in Indonesia - Hasan, Marvelina; Ismail, Dian Ekawaty; Moha, Mohamad Rivaldi (Information Technology and Science (ITScience), 2026)
The investigation system in Indonesian criminal procedure law is still dominated by a single authority approach that places the police as the primary actor. This model is increasingly questioned with the increasing complexity of modern crimes, the development of sectoral investigative institutions, and the emergence of Constitutional Court decisions rejecting the monopoly of investigative authority. This fragmentation of authority without a clear coordination design has the potential to give rise to institutional conflict and human rights violations. This study aims to formulate an ideal concept for implementing multiparty investigations in the Indonesian legal system that aligns with the principles of the rule of law, due process of law, and the protection of human rights. This study uses normative legal methods with statutory, conceptual, case-based, and comparative approaches. Data were obtained through a literature review of primary legal materials in the form of laws and court decisions, as well as secondary legal materials in the form of scientific journals, law books, and comparative studies of investigative systems in South Korea and the Netherlands. The results show that the practice of multiparty investigations in Indonesia has developed sectorally through the authority of the Corruption Eradication Commission (KPK), the National Narcotics Agency (BNN), and the Civil Servant Supervisory Agency (PPNS), but has not been integrated into a comprehensive criminal procedure law framework. Weak coordination, unclear boundaries of authority, and minimal judicial oversight increase the risk of inter-institutional conflict and violations of suspects' rights. Multiparty investigations require an integrated institutional design, a clear division of authority, horizontal coordination mechanisms, and strengthened judicial oversight to create a fair and effective criminal justice system.